Harm reduction: trends being disputed in health policies - Carla Regina Moreira; Cassia Baldini Soares; Celia Maria Sivalli Campos; Thais Helena Mourão Laranjo
ABSTRACT Objective: to identify the underlying harm reduction trends in Brazilian drug policies. Method: The research, qualitative in nature, used in-depth interviews with experts in the field. The recorded and transcribed material was analyzed via the content analysis method. Results: The analysis exposed the following conceptions: drug use is a disease, and its associated health practices should be treatment, rehabilitation and social reintegration. These conceptions deviate to some extent from the war on drugs approach, and support the adoption of harm-reduction practices, proposed by public health. Less expressively, critical conceptions which clearly distance themselves from the prohibitionist approach and from public health may be seen, in line with the perspective of collective health, for the implementation of emancipatory harm-reduction practices. Final considerations: Harm-reduction conceptions and practices reveal the underlying conservative, liberal, and critical tendencies in Brazilian drug policies.